Addition reaction of silicon with hydrogen solid supported bimetallic catalyst and its preparation method - YING,PENG BAI (2007)
The invention relates to the manufacturing of an accelerant. I has precious metal Pt, with deacidizing organic copper complex and inorganic carrier, processing the accelerant carrier with acid then filling into organic solution into paste, dropping into alcohol isopropylicum of the chloroplatinic acid, then the reacidizing organic copper complex, cooling and drying to get the accelerant. It improves activeness, optional feature of the Betasilicon affixture, with simple method, easy operation, with the accelerant conveniently for recirculation after the completion of the reaction. It has extensive use in application.